Konstruksi Teks Tale Ji Desa Tanjung Pauh Hilir Kerinci-Jambi: Kajian Antropolinguistik - Retmal Karnomo (Jurnal Ilmiah Dikdaya, 2020)
This research is qualitave descriptive reserach that aimed to explain; (1) The  transitivity structure of text of tale ji , (2) The Meaning of tale ji, and (3) Function of tale ji. The data are the texts of tale ji that uttered by the singers of tale Tanjung Pauh Hilir, Kerinci. This research was done through three steps: data collecting, data analysis, and data presentation.  Data collecting is used observational method in which tapping as the basic technique. The advance techniques used nonparticipant observational, recording, and note taking techniques. Data analysis used comparison (translational, referential, pragmatics) and distributional methods (deletion and assertion). The data presentation is formal and informal. Based on analysis, the researcher found that: 1) The structure of transitivity that construct the text of tale ji are: a. Process; material, mental, behavioral, verbal, and existential. b. Participant; goal, carrier, attributive, senser, actor, behavior, verbiage, owner, sayer, and receiver. c. Sirkumstance; manner, place, time. Alaa - alaa ii aa oon and alaa - la hu allooh which those functions are as musicallity, dzikir,and the borderer between lyrics of tale ji. 2) The meaning of tale ji are coneptual, affective, collocative, and contextual meaning. Conceptual meaning of tale ji is the representation of Islam teaching aplication. Affective meaning of tale ji is the mental representation between jamaah of hajj and society. Collocative meaning of tale ji is the representation of massages, hopes and praying of penale. Contextual meaning of tale ji is the representation of kinship. 3) The functions of tale ji are assertive, directive, comissive, and ekspressive.